2003
DOI: 10.1101/gr.1295503
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genome Analysis of Vibrio vulnificus, a Marine Pathogen

Abstract: The halophile Vibrio vulnificus is an etiologic agent of human mortality from seafood-borne infections. We applied whole-genome sequencing and comparative analysis to investigate the evolution of this pathogen. The genome of biotype 1 strain, V. vulnificus YJ016, was sequenced and includes two chromosomes of estimated 3377 kbp and 1857 kbp in size, and a plasmid of 48,508 bp. A super-integron (SI) was identified, and the SI region spans 139 kbp and contains 188 gene cassettes. In contrast to non-SI sequences, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
240
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(256 citation statements)
references
References 49 publications
13
240
1
2
Order By: Relevance
“…Toxins of the MARTX family are very large composite toxins. The 5,206-amino acid MARTX Vv toxin as found in the two sequenced strains of V. vulnificus, Korean isolate CMCP6 and Taiwanese isolate YJ016 (9,10), are 99% identical. Similar to all MARTX toxins, the majority of MARTX Vv is comprised of conserved repeat regions at the N and C termini that are proposed to form a pore in the eukaryotic cell plasma membrane for translocation of the central portion of the secreted toxin to the cytosol (11).…”
mentioning
confidence: 82%
“…Toxins of the MARTX family are very large composite toxins. The 5,206-amino acid MARTX Vv toxin as found in the two sequenced strains of V. vulnificus, Korean isolate CMCP6 and Taiwanese isolate YJ016 (9,10), are 99% identical. Similar to all MARTX toxins, the majority of MARTX Vv is comprised of conserved repeat regions at the N and C termini that are proposed to form a pore in the eukaryotic cell plasma membrane for translocation of the central portion of the secreted toxin to the cytosol (11).…”
mentioning
confidence: 82%
“…Recently, the sequence of the V. vulnificus RTX toxin (VvRtxA) was reported (14). The deduced primary amino acid sequences of VcRtxA and VvRtxA were compared and revealed that the two toxins are Ϸ80-90% identical throughout most regions of the toxins.…”
Section: Cholerae and Vibrio Vulnificus Rtx Toxins Have Unique Dommentioning
confidence: 99%
“…The Vibrionaceae comprise several dozen species that are often found associated with animal tissue (3). Among the small number of pathogenic Vibrio species that cause human diseases are Vibrio cholerae, Vibrio parahaemolyticus, and Vibrio vulnificus, the only members of the Vibrionaceae that have had their genome sequences reported (4)(5)(6). To date, no representative of the much more numerous benign and beneficial Vibrionaceae has been examined at the genome level.…”
mentioning
confidence: 99%